UMPSA Students Organize Perwira untuk Bumi Pertiwi Programme - Haslinda, Hashim; Nur Balqis Husna, Idris (UMPSA, 2023)
KUANTAN, 9 September 2023 - A total of 37 students from the Foundation in Science and Technology (AST), Centre for Science and Mathematics (PSM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), recently organized the "Perwira untuk Bumi Pertiwi" programme together with Sekolah Kebangsaan Pandan, Kuantan.